THE EFFECT OF PROFITABILITY, BOOK TAX DIFFERENCE AND TAX PLANNING ON INCOME MANAGEMENT IN AUTOMATICALLY SUB-SECTOR MANUFACTURING COMPANIES AND COMPONENTS REGISTERED IN INDONESIA STOCK EXCHANGE - Rayza Yonivan Bramasta; Yanti Budiasih (Yayasan Education and Social Center, 2021)
The purpose of this study is to determine the effect of profitability (net profit margin), book-tax differences, and tax planning on earnings management in Automotive Sub-Sector Manufacturing Companies and Components Listed on the Stock Exchange for the 2014-2019 Period. The method used in preparing this thesis is a quantitative method using secondary data based on the company’s financial statements that researchers got from the Indonesia Stock Exchange (IDX). The data analysis method used is the classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test) and hypothesis testing (multiple linear regression, t-test, F test and coefficient of determination). The results of this study indicate. Partially profitability does not have a significant effect on earnings management. Permanent difference partially has a significant effect on earnings management. Temporary differences partially have a significant effect on earnings management. Tax planning partially does not have a significant effect on earnings management